2015
DOI: 10.1021/jm501960u
|View full text |Cite
|
Sign up to set email alerts
|

3′-Functionalized Adamantyl Cannabinoid Receptor Probes

Abstract: The aliphatic side chain plays a pivotal role in determining the cannabinergic potency of tricyclic classical cannabinoids, and we have previously shown that this chain could be substituted successfully by adamantyl or other polycyclic groups. In an effort to explore the pharmacophoric features of these conformationally fixed groups, we have synthesized a series of analogues in which the C3 position is substituted directly with an adamantyl group bearing functionality at one of the tertiary carbon atoms. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 40 publications
2
42
0
Order By: Relevance
“…The above analysis indicated a critical role of the toggle switch residue Trp258 6.48 during CB2 activation and an essential function of arm 1 of the ligand for CB2 antagonism. Interestingly, our functional data showed that MRI2687 also acts as a partial agonist on CB1 ( Figure 6D), further supporting the notion that CB2 antagonist and CB1 agonist profiles probably occur in certain compounds (Ogawa et al, 2015), representing a CB2 and CB1 yin-yang functional relationship. The physiological im-plications of such opposing activation profiles between CB1 and CB2 are worth exploring further.…”
Section: Activation Mechanism Of Cb2supporting
confidence: 78%
“…The above analysis indicated a critical role of the toggle switch residue Trp258 6.48 during CB2 activation and an essential function of arm 1 of the ligand for CB2 antagonism. Interestingly, our functional data showed that MRI2687 also acts as a partial agonist on CB1 ( Figure 6D), further supporting the notion that CB2 antagonist and CB1 agonist profiles probably occur in certain compounds (Ogawa et al, 2015), representing a CB2 and CB1 yin-yang functional relationship. The physiological im-plications of such opposing activation profiles between CB1 and CB2 are worth exploring further.…”
Section: Activation Mechanism Of Cb2supporting
confidence: 78%
“…Cannabilactone analogs with modifications at the C3 side chain were prepared following the general method used for the synthesis of AM1710 (Scheme 3b-f). The design of these analogs was influenced by our earlier SAR work on the C3 side chain of tricyclic tetrahydrocannabinols (THCs) and hexahydrocannabinols (HHCs) [21,23,24,[28][29][30][31][32]. The addition of the larger cyclopentyl ring at C1 was attempted to explore the effect of the size of the benzylic substituents.…”
Section: Resultsmentioning
confidence: 99%
“…19,20 Our testing results (Table 2) show that all three compounds potently decreased the levels of cAMP, indicating that within this signaling mechanism these compounds behaved as potent agonists at both the CB1 and CB2 receptors with the 11-OH-HHC ester analogue 3b being the most potent.…”
Section: Functional Characterizationmentioning
confidence: 85%
“…We and others have observed that this condensation works well with resorcinols bearing electron donating alkyl side chains with bulky groups at the benzylic position including the 5-(1,1-dimethylheptyl)resorcinol. 1820,26 This, coupled with our earlier investigations on the mechanism of this condensation, 25 led us to postulate that presence of the carboxyester group in 13 decreases the electron density of the aromatic ring and slows down the rate of the initial Friedel–Crafts allylation reaction. Thus, the acid catalyzed decomposition of diacetates 14 to give 14a and the monoacetylation of 13 to give 13a become important side reactions.…”
Section: Chemistrymentioning
confidence: 96%
See 1 more Smart Citation